A Review of Passive Micromixers with a Comparative Analysis - Wasim Raza; Shakhawat Hossain; Kwang-Yong Kim (Micromachines, 2020)
A wide range of existing passive micromixers are reviewed, and quantitative analyses of ten typical passive micromixers were performed to compare their mixing indices, pressure drops, and mixing costs under the same axial length and flow conditions across a wide Reynolds number range of 0.01–120. The tested micromixers were selected from five types of micromixer designs. The analyses of flow and mixing were performed using continuity, Navier-Stokes and convection-diffusion equations. The results of the comparative analysis were presented for three different Reynolds number ranges: low-Re (Re ≤ 1), intermediate-Re (1 < Re ≤ 40), and high-Re (Re > 40) ranges, where the mixing mechanisms are different. The results show a two-dimensional micromixer of Tesla structure is recommended in the intermediate- and high-Re ranges, while two three-dimensional micromixers with two layers are recommended in the low-Re range due to their excellent mixing performance.